Characterization of a French series of female cases of mesothelioma. Issue 11 (13th August 2013) - Camiade, Elodie; Gramond, Celine; Jutand, Marthe‐Aline; Audignon, Sabyne; Rinaldo, Mickael; Imbernon, Ellen; Luce, Daniele; Galateau‐Sallé, Francoise; Astoul, Philippe; Pairon, Jean‐Claude; Brochard, Patrick; Lacourt, Aude
Abstract Background More than 80% of mesothelioma cases in men are attributable to occupational asbestos exposure compared to only 40% in women. The objective of the study was to characterize a series of female pleural mesotheliomas according to known and suspected risk factors. Methods From the exhaustive recording of 318 female mesothelioma cases in the French National Mesothelioma Surveillance Program between 1998 and 2009, multiple correspondence analysis and hybrid clustering were performed to characterize these cases according to expert assessed occupational and non‐occupational exposure to asbestos and man‐made vitreous fibers, X‐ray exposure, and history of cancer and non‐malignant respiratory diseases. Results Four clusters were identified: (1) occupational exposure to asbestos and man‐made vitreous fibers (7.9% of subjects); (2) radiation exposure during radiotherapy (12.9%); (3) increased asbestos exposure (19.8%); and (4) "non‐exposure" characteristics (59.4%). Conclusion These results will allow hypotheses to be generated about associations between mesothelioma and non‐occupational asbestos exposure, X‐ray exposure and history of respiratory disease. Am. J. Ind. Med. 56:1307–1316, 2013. © 2013 Wiley Periodicals, Inc.